Total anatomic vascular dissection for lobectomy by using only energy devices - Gonzalez-Rivas, Diego (Journal of Visualized Surgery, 2015)
Background: The introduction of ultrasonic energy into surgical dissecting devices was a technological breakthrough in minimally invasive surgery in the 1990s. Methods: Nowadays, the energy devices are used very often during video-assisted thoracoscopic surgery (VATS) especially for lymph node dissection and for transection of small pulmonary vessels. However these devices can be used for hilar anatomic dissection in expert hands. Results: In this video we show a right lower lobectomy performed by uniportal VATS in where the anatomic dissection of artery, vein and bronchus was performed by only using an ultrasonic energy device (Harmonic scalpel). The total surgical time for lobectomy was 30 minutes and 20 minutes for lymph node dissection. Conclusions: The use of energy devices for vascular and bronchial dissection during lobectomy is feasible and safe when performed by expert thoracoscopic surgeons.